(3eONd Edi GdEPGYGJ GdeMdjI aj GdYGde h bVGjG GdeLJeY (B/s - (3SYjOGjfj, SdGejs; (3Hf jejfIs ((3GdLRGFQ (B:s (3OGQ GdNdOhfjI ddfTQ h GdJhRjY ,s, 2016)
(3JeKd GdJfejI GMO GdYhGed h GdOhGaY GdGSGSjI dGfTGA GdGPGYGJ GdeMdjI ef GLd JaYjd GdeTGQcI aj GdJfejI MjK Gf GdOhd GdfGejI dG JSJWjY Gf JMbb GgOGa GdJfejI Ohf Gf Jhdi GgJeGeG HGaQGOgG aj eLJeYGJge GdeMdjI h bO GOQcJ Ohd YOjOI Gf GaVd GSGdjH GdGYdGe dJMbjb eTGQcI aYGdI ef LGfH GdLeGgjQ aj NWW HQGeL GdJfejI gh GdhUhd Gdi gPg GdLeGgjQ aj HjFGJge GdeMdjIs
(3HHdjhZQGajG (B: (3U(B.109-119s
Keywords: (3GdJdaRjhfs; (3hSGFd GdEYdGes; (3GdEPGYIs